Gakkel Ridge Major & Trace Elements - Langmuir, Charles (IEDA: EarthChem Library, 2011)
Abstract: The data set contains major oxide data for volcanic glasses of samples collected along the Gakkel Ridge on the Healy 0102 and Polarstern 59 cruises collected by microprobe at the American Museum of Natural History, and trace element data collected by solution and laser ICP-MS, as well as station data for the samples.